Occurrence of E. coli O157:H7 and Listeria monocytogenes and Identification of Hazard Analysis Critical Control Points (HACCPs) in Production Operations of a Typical Tropic Cheese 'Wara' and Yoghurt - Adetunji, Victoria O.; Arigbede, Mary I. (Pakistan Journal of Nutrition, 2011)
Critical Control Points (CCPs) associated with the processing of cheese in five local cheese factories and yoghurt in two conventional processing factories, located in Ilorin, Kwara state, Nigeria were identified using flow diagrams and microbial assay for detection of E. coli and Listeria monocytogenes. Fifty-eight (58) samples were collected along the processing lines. The CCPs identified were reception of raw milk, addition of coagulant, curdling point and cheese in moulds for cheese processing, while for yoghurt processing, powdered milk, pasteurization, addition of inoculum, fermentation and the finished product were the CCPs. In all the factories evaluated, E. coli and Listeria monocytogenes were observed to be present throughout the processing line with the finished product containing a significant level (p